Announcing new members of the Advisory Editorial Board - Owczuk, Radosław; Zdanowski, Szymon (Anestezjologia Intensywna Terapia, 2021)
We on the Editorial Board of “Anaesthesiology Intensive Therapy” are committed to continuous improvement of the quality of our journal, and thus we are excited that two excellent clinician-scientists have joined us in this endeavour. It is our great honour to announce that Doctor Thomas Kander of Lund University (Sweden) and Doctor Dan Drzymalski of Tufts Medical Center (Boston, Massachusetts) have become members of the Advisory Editorial Board of “Anaesthesiology Intensive Therapy”. Doctor Thomas Kander